Architectural and spatial organization of Muslim educational institutions in Kazakhstan in the medieval period - Issina А.З.; Ozganbayeva Б.Е.; Kaliyev Д.О. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2022)
The article is given to consider the issues of madrasahs in Kazakhstan at diverse time stages of the medieval period. The overwhelming significance of old madrasahs within the structure of the city and past is considered. The study is analyzing inclinations within the plan of madrasahs, issues of arrangement of architectural arranging, utilitarian and compositional arrangements. Taking under consideration the pertinence of the strategic importance of these objects which are the legacy of the Turkic-speaking states, within the future, it foreordained the reason of the consideration of this article - to recognize the most bunches of factors that affected the compositional strategies of organizing spaces. Based on this purpose, the accessible chronicled materials made it conceivable to decide the objectives of the study: – uncovering the part of madrasah as a key structure of Islamic education; – investigation of the components affecting the method of shaping; – assurance of the specifics of the building and arrange We advertised the strategy to uncover the philosophical meaning of the structural composition of instructive teaches as a chunk of craftsmanship. The town-planning highlights, structural and imaginative characteristics of the objects of the investigation are described based on the hunt for approaches to the plan of madrasahs where the contact of the ideological views of Islam and the Turkic conventions, both profoundly and structurally is revealed. As a result, the essential guideline within the plan of madrasahs was uncovered. This guideline demonstrates that they were city-forming objects. This made it conceivable to assist recognize the essential standards of Kazakh conventional design of the medieval period. The method of the research moreover analyzes the method of separation of building parameters and changes within the space-planning structure of the objects beneath thought. As a result, a bunch of variables that influenced these changes is determined. The best structural methods and building arrangements within the organization of a favorable discuss conditioning framework of a building beneath the characteristic and climatic conditions of the southern, western and central locales of Kazakhstan have been distinguished which moreover had a noteworthy impact on the arrangement of instructive institutions.